Oxidative stress as a pathway linking maternal phthalate and bisphenol exposure to childhood allergy and lung function: Mediation and interaction analyses - Thomas Boissiere-O'Neill; Nina Lazarevic; Anne-Louise Ponsonby; Peter D. Sly; Aimin Chen; Tamara L. Blake; Cassidy Du Berry; Louise King; Cindy Pham; Samuel Tanner; Sarah Thomson; Dwan Vilcins (Environmental Research, 2026)

Impact of clay treatment on aviation fuel thermal stability - Carlie Anderson; Amanda Mae Arts; Susan Mueller; Linda Shafer; Richard Striebich; Samuel Tanner; Paul Wrzesinski; Steven Zabarnick; Zachary West (Fuel, 2026)

Tissue‐Specific Plasticity of DNA Methylation Across Intertidal Microhabitats in Juvenile Mussels ( Mytilus californianus ) - Qiting Cai; Samuel N. Bogan; Richelle L. Tanner; Joanna L. Kelley; W. Wesley Dowd (Molecular Ecology, 2026)
Epigenetic modifications to DNA are proposed to underpin plastic responses to environmental change, and the manner in which DNA methylation contributes to plasticity likely differs among tissues. However, few studies have investigated tissue‐specific DNA methylation responses to ecologically relevant environmental stressors in natural settings. Here, we used reduced representation bisulfite sequencing to examine the influence of in situ microhabitats on DNA methylation in gill and foot of juvenile California mussels ( Mytilus californianus ), a foundation species with widespread dispersal and little evidence of genetic population structure. We examined mussels from a one‐month reciprocal transplant experiment between a cool, wave‐exposed and a warm, wave‐protected microhabitat. These manipulations—which were previously shown to alter juvenile mussels' heat tolerance—led to significant and tissue‐specific changes in CpG methylation, including within a number of genes with roles in stress response pathways. Differentially methylated genes were involved in processes including heat shock response, proteolysis, and temperature sensing. In gills, differentially methylated CpGs were more likely to occur in introns relative to other inter‐ and intragenic features. This study expands on previous research that examined environmentally driven shifts in DNA methylation by documenting plastic and tissue‐specific changes in DNA methylation between microhabitats in a natural setting.

A pathway-based genetic score for inflammation: An indicator of vulnerability to phthalate-induced adverse neurodevelopment outcomes - Ahmed Elagali; Alex Eisner; Samuel Tanner; Katherine Drummond; Christos Symeonides; Chloe Love; Mimi LK. Tang; Toby Mansell; David Burgner; Fiona Collier; Peter D. Sly; Martin O'Hely; et al. (International Journal of Hygiene and Environmental Health, 2025)

Enhanced analysis of cellulose nanofibril film structure - Hans Estrella Cainglet; D. Mark Martinez; James Drummond; Samuel N.M. Brown; Gil Garnier; Joanne Tanner; Warren Batchelor (Carbohydrate Polymers, 2025)

Using fiber-optic distributed temperature sensing in fisheries applications: An example from the Ozark Highlands - Skylar L. Wolf; Dusty A. Swedberg; Evan P. Tanner; Samuel D. Fuhlendorf; Shannon K. Brewer (Fisheries Research, 2023)

Fire management alters the thermal landscape and provides multi‐scale thermal options for a terrestrial turtle facing a changing climate - Ellen P. Robertson; Evan P. Tanner; R. Dwayne Elmore; Samuel D. Fuhlendorf; Jonathan D. Mays; Jennifer Knutson; John R. Weir; Scott R. Loss (Global Change Biology, 2022)
As effects of climate change intensify, there is a growing need to understand the thermal properties of landscapes and their influence on wildlife. A key thermal property of landscapes is vegetation structure and composition. Management approaches can alter vegetation and consequently the thermal landscape, potentially resulting in underappreciated consequences for wildlife thermoregulation. Consideration of spatial scale can clarify how management overlaid onto existing vegetation patterns affects thermal properties of landscapes relevant to wildlife. We examined effects of temperature, fire management, and vegetation structure on multi‐scale habitat selection of an ectothermic vertebrate (the turtle Terrapene carolina triunguis ) in the Great Plains of the central United States by linking time‐since‐fire data from 18 experimental burn plots to turtle telemetry locations and thermal and vegetation height data. Within three 60‐ha experimental landscapes, each containing six 10‐ha sub‐blocks that are periodically burned, we found that turtles select time‐since‐fire gradients differently depending on maximum daily ambient temperature. At moderate temperatures, turtles selected sub‐blocks with recent (

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Using aerial surveys and citizen science to create species distribution models for an imperiled grouse - Ashley M. Tanner; Evan P. Tanner; Monica Papeş; Samuel D. Fuhlendorf; R. Dwayne Elmore; Craig A. Davis (Biodiversity and Conservation, 2020)

Kin grouping is insufficient to explain the inclusive fitness gains of conspecific brood parasitism in the common eider - Samuel D. Hervey; Andrew F. Barnas; Tanner J. Stechmann; Robert F. Rockwell; Susan N. Ellis‐Felege; Brian J. Darby (Molecular Ecology, 2019)
Conspecific brood parasitism allows females to exploit other females' nests and enhance their reproductive output. Here, we test a recent theoretical model of how host females gain inclusive fitness from brood parasitism. High levels of relatedness between host and parasitizer can be maintained either by: (a) kin recognizing and parasitizing each other as a form of cooperative breeding or (b) natal philopatry and nest site fidelity facilitating the formation of kin groups, thereby increasing the probability of parasitism between relatives nesting in close proximity. To address these two hypotheses we genotyped feathers and hatch membranes of common eiders ( Somateria mollissima ) from western Hudson Bay, Canada, using a noninvasive sampling methodology. We found that most instances of brood parasitism do result in inclusive fitness gains. Furthermore, females with failed nests moved an average of 492 m from their previous year's nest site, while successful females only moved an average of 13 m. Therefore, we observed host–parasite relatedness can occur at levels higher than would be expected by chance even in the absence of kin grouping, suggesting that closely related females nesting near one another is not essential to maintain high host–parasitizer relatedness. In addition, kin grouping is only a transient phenomenon that cannot occur every year due to the propensity for females of failed nests to nest farther away from their nest site in subsequent years than females with successful nests, which provides support for kin recognition as a more likely mechanism to maintain high host–parasitizer relatedness over time.

Regional leukoaraiosis and cognition in non-demented older adults - Margaret E. Wiggins; Jared Tanner; Nadine Schwab; Samuel J. Crowley; Ilona Schmalfuss; Babette Brumback; David J. Libon; Kenneth Heilman; Catherine C. Price (Brain Imaging and Behavior, 2019)

Erratum to: Considering total intracranial volume and other nuisance variables in brain voxel based morphometry in idiopathic PD - Samuel Crowley; Haiqing Huang; Jared Tanner; Qing Zhao; Nadine A. Schwab; Loren Hizel; Daniel Ramon; Babette Brumback; Mingzhou Ding; Catherine C. Price (Brain Imaging and Behavior, 2018)

Considering total intracranial volume and other nuisance variables in brain voxel based morphometry in idiopathic PD - Samuel Crowley; Haiqing Huang; Jared Tanner; Qing Zhao; Nadine A. Schwab; Loren Hizel; Daniel Ramon; Babette Brumback; Mingzhou Ding; Catherine C. Price (Brain Imaging and Behavior, 2018)

Extreme climatic events constrain space use and survival of a ground‐nesting bird - Evan P. Tanner; R. Dwayne Elmore; Samuel D. Fuhlendorf; Craig. A. Davis; David K. Dahlgren; Jeremy P. Orange (Global Change Biology, 2017)
Two fundamental issues in ecology are understanding what influences the distribution and abundance of organisms through space and time. While it is well established that broad‐scale patterns of abiotic and biotic conditions affect organisms’ distributions and population fluctuations, discrete events may be important drivers of space use, survival, and persistence. These discrete extreme climatic events can constrain populations and space use at fine scales beyond that which is typically measured in ecological studies. Recently, a growing body of literature has identified thermal stress as a potential mechanism in determining space use and survival. We sought to determine how ambient temperature at fine temporal scales affected survival and space use for a ground‐nesting quail species ( Colinus virginianus ; northern bobwhite). We modeled space use across an ambient temperature gradient (ranging from −20 to 38 °C) through a maxent algorithm. We also used Andersen–Gill proportional hazard models to assess the influence of ambient temperature‐related variables on survival through time. Estimated available useable space ranged from 18.6% to 57.1% of the landscape depending on ambient temperature. The lowest and highest ambient temperature categories ( 35 °C, respectively) were associated with the least amount of estimated useable space (18.6% and 24.6%, respectively). Range overlap analysis indicated dissimilarity in areas where Colinus virginianus were restricted during times of thermal extremes (range overlap = 0.38). This suggests that habitat under a given condition is not necessarily a habitat under alternative conditions. Further, we found survival was most influenced by weekly minimum ambient temperatures. Our results demonstrate that ecological constraints can occur along a thermal gradient and that understanding the effects of these discrete events and how they change over time may be more important to conservation of organisms than are average and broad‐scale conditions as typically measured in ecological studies.